Natural Law and the Rhetoric of Empire: Reynolds v. United States, Polygamy, and Imperialism - Nathan B. Oman (Washington University Law Review, 2011)
In 1879, the U.S. Supreme Court construed the Free Exercise Clause for the first time, holding in Reynolds v. United States that Congress could punish Mormon polygamy. Historians have interpreted Reynolds, and the anti-polygamy legislation and litigation that it midwifed, as an extension of Reconstruction into the American West. This Article offers a new historical interpretation, one that places the birth of Free Exercise jurisprudence in Reynolds within an international context of Great Power imperialism and American international expansion at the end of the nineteenth century. It does this by recovering the lost theory of religious freedom that the Mormons offered in Reynolds, a theory grounded in the natural law tradition. It then shows how the Court rejected this theory by using British imperial law to interpret the scope of the First Amendment. Unraveling the work done by these international analogies reveals how the legal debates in Reynolds reached back to natural law theorists of the seventeenth century, such as Hugo Grotius, and forward to fin de siècle imperialists, such as Theodore Roosevelt. By analogizing the federal government to the British Raj, Reynolds provided a framework for national politicians in the 1880s to employ the supposedly discredited tactics of Reconstruction against the Mormons. Embedded in imperialist analogies, Reynolds and its progeny thus formed a prelude to the constitutional battles over American imperialism in the wake of the Spanish-American War. These constitutional debates reached their denouement in the Insular Cases, where Reynolds and its progeny appeared not as Free Exercise cases but as precedents on the scope of American imperial power. This Article thus remaps key events in late nineteenth-century constitutional history, showing how the birth of Free Exercise jurisprudence in Reynolds must be understood as part of America’s engagement with Great Power imperialism and the ideologies that sustained it.
Keywords: Natural law; Imperialism – Great Britain; United States – Territorial expansion; Polygamy; Free exercise clause (Constitutional law); Reconstruction (U.S. history; 1865-1877); Constitutional history; Reynolds v. United States